Peran Satuan Polisi Pamong Praja (Satpol PP) dalam Menertibkan Bangunan Liar di Kecamatan Bagan Sinembah Kabupaten Rokan Hilir Provinsi Riau - Agustinus Pandiangan; Abdul Kadir; Yurial Arief Lubis (Universitas Medan Area, 2023)
This research is aimed to know the role of Public Order Agency in curbing illegal buildings especially for regulation, institution, and human resources in the implementation of that role. The problems on this research would discuss about: 1) The role of Public Order Agency in curbing illegal buildings in Bagan Sinembah, Rokan Hilir, Riau. 2) The factors which became an obstacle for Public Order Agency in curbing illegal buildings in Bagan Sinembah, Rokan Hilir, Riau. This research used qualitative method as a data analysis method in the office of Public Order Agency. The source of data on this research is the head of Public Order Agency, the head of public order and a public comfort, the member of Public Order Agency, sub-district office employee of Bagan Sinembah and the society affected by the enforcement. The data were collected based on doing an interview and documentation. The result of this research showed that the role of Public Order Agency in curbing illegal buildings in Bagan Sinembah, Rokan Hilir, Riau started from socialization, data collection, an appeal, until the control was done.